2006
DOI: 10.1097/01.inf.0000214998.16248.b7
|View full text |Cite
|
Sign up to set email alerts
|

T280M Variation of the CX3C Receptor Gene Is Associated With Increased Risk for Severe Respiratory Syncytial Virus Bronchiolitis

Abstract: Our findings support the hypothesis of the pivotal role of the G glycoprotein CX3CR1 pathway in the pathogenesis of RSV bronchiolitis and propose CX3CR1 as a potential therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 32 publications
0
38
0
1
Order By: Relevance
“…Recent studies have demonstrated that inflammatory mediators play essential roles in enhancing respiratory viral pathologies [15][16][17][18][19]; however, several of these mediators have not yet been identified. The contribution of host immune responses to the pathologies observed during respiratory viral infections opens up the potential for therapeutic alternatives based on the suppression of pathogenic immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that inflammatory mediators play essential roles in enhancing respiratory viral pathologies [15][16][17][18][19]; however, several of these mediators have not yet been identified. The contribution of host immune responses to the pathologies observed during respiratory viral infections opens up the potential for therapeutic alternatives based on the suppression of pathogenic immune response.…”
Section: Introductionmentioning
confidence: 99%
“…For example, CX3CR1 polymorphisms have been implicated in conditions such as Crohn's disease, multiple sclerosis, and bronchiolitis among Caucasians [25][26][27]. Further downplaying the possible role of CX3CR1 genetic polymorphism on HIV infection, no significant differences in CX3CR1 745G>A genotype and allele frequencies between HIV EI and EU children were observed (Table 3).…”
Section: Chemokine Receptor Polymorphism and Their Association With Hmentioning
confidence: 84%
“…'lar›, CX 3 CR1 Thr280Met SNP'de fliddetli RSV bronfliyolit riskinin artm›fl oldu¤unu göstermifllerdir. Bu mutasyon, hem virüslerin giriflini kolaylaflt›rarak, hem de viral klirens etkinli¤ini azaltarak uygunsuz uyar› ve immünopato-jenik immün yan›ta neden olmaktad›r (47).…”
Section: Akut Bronfliyolitte Immün Yan›t Ve Doku Hasar› Iliflkisiunclassified